VIGOR BENIH BEBERAPA VARIETAS JAGUNG PADA MEDIA TANAM TERCEMAR HIDROKARBON - Syafruddin Syafruddin; Taqur Miranda (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
The objectives of this research were to assess effects of varieties and hydrocarbon-contaminated growing medium on seed vigors of corn and interactions between the two factors mentioned. The experimental design used was a completely randomized design 3 x 4 with three replications. The first factor was varieties, consisting three varieties, namely, Pertiwi 3, Manise, and Bonanza F1. The second factor was hydrocarbon-contaminated growing medium, consisting four levels of hydrocarbon (crude oil) concentration i.e. without crude oil, 5 ml crude oil/liter water, 10 ml crude oil/liter water and 15 ml crude oil/liter water. The result showed that some varieties significantly affect potential of seed growth, seed germination, rate of germination, vigor index and seed germination uniformity. However, concentration of hydrocarbon did not significantly affect all parameter observed. There was significant interaction between varieties and concentration of hydrocarbon on potential of seed growth, seed germination uniformity and T.50.